Analysis Of Financial Ratios And Macroeconomic Factors To Stock Return And Swot Strategy (case Study: Finance Sector Companies Listed In Indonesia Stock Exchange Year 2010-2014) - Fathia Rahma Kamila; Endang Chumaidiyah; Rita Zulbetti (eProceedings of Engineering, 2016)
This study was conducted to examine the influence of Earning Per Share (EPS), Debt To Equity Ration (DER), Return On Asset (ROA), inflation, BI Rate, and Exchange Rate partially and simultaneously to the finance sector’s stock returns. Besides, this study aims to analyze the strategy for finance sector to improve the performnace and the stock return. The sample used were 36 companies from 59 finance companies listed in Indonesia Stock Exchange during periode 2010-2011 so that the data processed is 180 samples. The analytical tool is data panel regression analysis with the classical assumption tests and the model test. The result of this study showed that only ROA, inflation, and BI Rate partially has significant influence on stock return while simultaneously EPS, DER, ROA, inflation, BI Rate, and Exchange Rate has significant influence on the stock return. Then, based on the analysis of stock return in 2010-2014, Bank QNB Indonesia can represent the finance sector to indetified the current performance and analyzed the strategy. The strategy formulation was conducted by describing the strengths, wekanesses, opportunities, and threats. Then it could be determined the competitive posistion and formulate the strategy. This study used SWOT analysis, AHP, and SWOT Diagram. Keywords: Earning Per Share, Debt To Equity Ratio, Return OnAsset, Inflation, BI Rate, Exchange Rate, Strategy, AHP Method, SWOT